Optimization of roselle tea bag brewing by variation of particle weight and type of tea bags - Ike Sitoresmi Mulyo Purbowati; Ali Maksum; Gunawan Wijonarko; Sania Rizqia; Ngo Pham Thao Nguyen (Agroindustrial Technology, University of Trunojoyo Madura, 2026)
Roselle flower petals contain bioactive compounds such as anthocyanin and vitamin C which function as primary antioxidants and can clinically improve the body's immune system. To improve the body's immune system, you can consume roselle in the form of herbal tea. There are several important aspects that must be considered when making herbal tea bags, such as the weight of the tea particles and the type of tea bag used. This research aims to determine the optimization of the properties of brewing roselle tea bags with variations in particle weight and type of tea bag and to determine the physicochemical and sensory characteristics of brewing roselle tea bags under optimum conditions. The research was carried out using the Response Surface Methodology (RSM) optimization method using Design Expert version 13 software with an Optimal Custom Design experimental design. The results of the research showed that the optimal brewing of roselle tea bags was by varying the particle weight treatment of 3.82 grams using nylon tea bags. The physicochemical characteristics of brewing roselle tea bags under optimum conditions are anthocyanin content (7.464±0.355 mg/L), antioxidant activity (92.47%), vitamin C content (2.534 mg/g), pH (2.47) and color. lightness (15.38) redness (-1.95) and yellowness (3.46). The sensory characteristics of brewing roselle tea bags under optimum conditions are that they have a distinctive aroma of roselle, the taste tends to be very sour, the color is slightly dark red, produces an astringent aftertaste and the panelists' preference for the product is neutral.